Harmonization of Biosafety and Biosecurity Standards for High-Containment Facilities in Low- and Middle-Income Countries: An Approach From the Perspective of Occupational Safety and Health - Maehira, Yuki; Spencer, Robert C. (Frontiers in Public Health, 2019)
Following the global-level Ebola virus disease (EVD) outbreak during 2014–2016, international collaboration with multi-organizational participation has rapidly increased, despite the quantitative and qualitative lack of high-containment laboratory facilities in low- and middle-income countries (LMICs). While global health security has been given greater priority, human security readiness tends to be neglected in both advanced countries and LMICs to where limited global human resources are to be deployed for Biosafety Level-4 (BSL-4) investigations. They are being selectively deployed to implement medical research and development (R&D) investigations. Those experts dispatched from advanced countries bring a long list of scientific tasks with high-tech devices, supplies, and training programs to introduce their collaboration with local partners in LMICs, where biological targets for investigation are located near to their natural habitats,, and subsequently realize the list becomes endless to establish their basic high-containment laboratory functions. Prioritizing scientific and managerial success to make laboratory organization more efficient and productive, most laboratory safety policies have focused on the functionality of technical skills or performance, procedural methodologies, and supervision or guidance of employees, particularly in LMICs, through training in technical expertise. However, such approaches have mostly been developed on an institutional basis, and there is no contextual integration of the safety policies in international R&D settings. Therefore, frontline experts have continuously suffered from the risks and hazards of infection and their concerns have not changed to secure qualified scientific outcomes in LMICs, many of which around the world feature politically unstable work environments. Having conducted a quick review of the key biosafety and biosecurity management documents, relevant policy analyses, and research, we identified aspects of occupational safety and health (OSH) that had been insufficiently recognized as key bottlenecks, or probable drivers with which we can make further strategic interventions to reorient, harness infection risk-based vertical approaches, and harmonize policies and standards for biosafety and biosecurity, particularly in the context of international BSL-4 collaboration in LMICs.